Optimalisasi Peran Pendamping untuk Keberhasilan Usaha Tenaga Kerja Mandiri Lanjutan - Melva Sitorus (Jurnal Pengembangan Ketenagakerjaan, 2025)
This policy paper addresses the challenges observed in the field regarding the assignment of mentors, which has not been optimally supporting the success of Advanced Independent Labor (TKM Lanjutan). The role of mentors is crucial; however, it is currently limited in several areas, including the duration of mentoring sessions, the motivation and commitment of TKM Lanjutan participants, the competencies of the mentors, the ability of TKM Lanjutan to leverage technology, and the alignment between the number of mentors and the TKM Lanjutan they support. In crafting this policy paper, the author employed a literature review method to grasp relevant concepts and theories, and to examine existing findings. Additionally, an inventory of necessary data was conducted, alongside the collection of pertinent reference materials. This policy paper aims to formulate actionable policy recommendations for the Ministry of Manpower, particularly regarding enhancing the mentoring assignments to further bolster the success of TKM Lanjutan, with a primary focus on the duration of mentoring sessions. Ultimately, this policy paper aspires to provide valuable insights for the Ministry of Manpower, particularly for the Directorate of Labor Opportunity Expansion, as they work to enhance the effectiveness of TKM Lanjutan initiatives.